Trabalho emocional dos militares do Exército Brasileiro nas missões de paz das Nações Unidas - Costa, William Trajano de Andrade (2011)
The emotional labor (TE) was a concept coined by Hochshild in 1983, meaning the management of their own emotions or the other to present a face required by the organization. Studies on the TE developed in many ways, especially in relation to research methodologies, gender issues and their consequences. The present research related to this last line, confirmed the applicability of the model of cause and effect of Newman, Guy, and Mastracci (2008) in TE executed by Brazilian Army‟s (EB) militaries in peacekeeping missions of the United Nations, using the methodology of structural equations. Qualitative analysis of the data also allowed us to identify specific features: the most important dimension of the TE in that context is related to interpersonal relationship management of subordinates by superiors.